Small molecular weight alginate gel porogen for the 3D bioprinting of microvasculature - Vanlauwe, Florian; Dermaux, Charlotte; Shamieva, Sabina; Vermeiren, Stef; Van Vlierberghe, Sandra; Blondeel, Phillip (Frontiers in Bioengineering and Biotechnology, 2024)
In order to recreate the complexity of human organs, the field of tissue engineering and regenerative medicine has been focusing on methods to build organs from the bottom up by assembling distinct small functional units consisting of a biomaterial and cells. This bottom-up engineering requires bioinks that can be assembled by 3D bioprinting and that permit fast vascularization of the construct to ensure survival of embedded cells. To this end, a small molecular weight alginate (SMWA) gel porogen is presented herein. Alginate is a biocompatible biomaterial, which can be easily converted into small porogen gels with the procedure reported in this article. The SMWA porogen is mixed with photo-crosslinkable hydrogels and leached from the hydrogel post-crosslinking to increase porosity and facilitate vascularization. As a proof of concept, this system is tested with the commonly used biomaterial Gelatin Methacryloyl (GelMA). The SMWA porogen-GelMA blend is proven to be bioprintable. Incubating the blend for 20 mins in a low concentration phosphate buffered saline and sodium citrate solution significantly reduces the remaining porogen in the hydrogel. The intent to always completely leach the porogen was abandoned, as longer incubation times and higher concentrations of phosphate and citrate were detrimental to endothelial proliferation. Nonetheless, even with remnants of the porogen left in the hydrogel, the created porosity significantly improves viability, growth factor signaling, vasculogenesis, and angiogenesis in 3D bioprinted structures. This article concludes that the usage of the SMWA porogen can improve the assembly of microvasculature in 3D bioprinted structures. This technology can benefit the bottom-up assembly of large scaffolds with high cell density through 3D bioprinting by improving cell viability and allowing faster vascularization.